Brazilian Peppertree Control - Kenneth T. Gioeli; Stephen F. Enloe; Carey Minteer; Kenneth Langeland (EDIS, 2018)
Brazilian peppertree is a nonnative invasive tree widely distributed in central and southern Florida.  This fact sheet provides readers with the Brazilian peppertree history in Florida, habitats where found, identification, biology and control recommendations.  The control recommendations in this fact sheet include traditional herbicide strategies as well as innovative new applications of biological control.